Aim, focus, shoot: The choice of appropriate and effective macroprudential instruments - Michele Azzone; Mara Pirovano (European Central Bank (ECB), 2024)
We examine the issue of the appropriate selection of macroprudential instruments according to the vulnerabilities identified and the policymakers' objectives using a version of the 3D DSGE model following Mendicino et al. (2020) and Hinterschweiger et al. (2021) calibrated for the euro area. We consider a broad set of macroprudential instruments, including broad and sectoral countercyclical capital requirements, LTV and LTI limits and assess their transmission channels as well as their effectiveness in mitigating rising broad and sectoral vulnerabilities. We find that sectoral instruments are most effective to increase bank resilience to sectoral risks, limiting spillover effects. LTI limits are superior to LTV limits in containing the growth of mortgage credit and household indebtedness. Finally, we find that macroprudential policy is better suited than monetary policy to address emerging real estate-related imbalances.
Keywords: E44; E58; G21; G28; 330; Financial stability; Banking regulation; Macroprudential policy; Countercyclical capital buffer; DSGE